Rugosidad superficial de resinas nanohíbridas pulidas con copas de silicona y pasta diamantada versus discos Sof-lex - Benancio Gil, Monar Monar (2020)
Today there is a wide variety of resin polishing systems, but there is still no consensus on the material or polishing system that allows us to obtain less surface roughness, so that dental restoration will be durable and aesthetically better. It has been considered that there are materials that have given very good results for the polishing of resins, therefore two of them were chosen to analyze which shows less roughness. The objective of this research was to analyze two polishing systems on the surface roughness of nanohybrid resins. Twenty nanohybrid resin samples of 10 mm in diameter and 3 mm thick were made, they were divided into 2 groups of 10 samples each. The first group was polished with silicone cups and diamond paste. The second collection was polished with Sof-Lex discs. The measurement was performed with the SURFTEST SJ-210 surface roughness meter. Once the study was done, it was possible to determine the system with more roughness of polishing and it was the group of resin samples with Sof-Lex discs, with a minimum value of 0.191 µm and a maximum of 0.358 µm. But the best system was the samples of resin polished with silicone cups and diamond paste with a minimum of 0.089 µm and a maximum of 0.225 µm. The ratings obtained in the resin exposed samples in this study determine that resins polishing with silicone cups and diamond paste obtain less surface roughness.